2013
DOI: 10.1016/j.atherosclerosis.2013.07.053
|View full text |Cite
|
Sign up to set email alerts
|

The prospective association of Chlamydia pneumoniae and four other pathogens with development of coronary artery calcium: The Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Objective Previous basic and cross-sectional studies obtained conflicting results regarding the association of pathogens with coronary artery calcium (CAC). The aim of this study is to prospectively evaluate this association in a population-based cohort. Methods We examined 5,744 individuals aged 45-84 years at baseline (2000-02) who underwent repeated CAC assessment on average 2.4 years later (a half at visit 2 [2002-04] and the other half at visit 3 [2004-05]). CAC incidence was defined as newly detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…On the other hand, Laek et al. studied a possible correlation between positivity to infectious agents, such as C. pneumoniae , H. pylori, cytomegalovirus, herpes simplex virus, and hepatitis A virus, and coronary artery calcium (CAC) but with negative findings.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Laek et al. studied a possible correlation between positivity to infectious agents, such as C. pneumoniae , H. pylori, cytomegalovirus, herpes simplex virus, and hepatitis A virus, and coronary artery calcium (CAC) but with negative findings.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Sealy-Jefferson et al [10] demonstrated that antibody levels to H. pylori predicted the incidence of strokes in a Mexican-American population (OR: 1.58; 95% CI: 1.09-2.28). On the other hand, Laek et al [11] studied a possible correlation between positivity to infectious agents, such as C. pneumoniae, H. pylori, cytomegalovirus, herpes simplex virus, and hepatitis A virus, and coronary artery calcium (CAC) but with negative findings.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…A number of epidemiologic studies report a significant correlation of cardiovascular disease or its risk factors with H. pylori infection6891011. However, the results of several other studies failed to confirm the association121314.…”
mentioning
confidence: 99%
“…However, contrary to the results of the clinical studies and a recent meta-analysis that suggested a closer relationship between the HP infection and the risk and outcomes of AMI and ACS, 2 data about a link between HP infection and chronic CAD are inconsistent. 4 13 …”
Section: Discussionmentioning
confidence: 99%
“… 2 At the same time, data regarding a link between HP infection and chronic CAD are inconsistent. 4 13 Therefore, we aimed to test a correlation between HP infection and the severity of coronary atherosclerosis in patients with chronic CAD. Assuming that HP infection represents an independent CAD risk factor, more severe coronary atherosclerosis was expected in HP-positive patients.…”
Section: Introductionmentioning
confidence: 99%